Microstructure and hot deformation behavior of the Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy. (June 2022) - Tang, Shunlong; Zhou, Meng; Li, Xu; Zhang, Yi; Xu, Deye; Zhang, Zhiyang; Tian, Baohong; Jia, Yanlin; Liu, Yong; Volinsky, Alex A.; Marchenko, Ekaterina S.
Abstract: The Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy was prepared by vacuum induction melting. The hot deformation experiments with the alloy were carried out using the Gleeble-1500 deformation simulation device at 0.001–10 s −1 strain rate, and 500–900 °C deformation temperature. The hot working constitutive equation for the Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy was established. The optimal hot processing of the Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy is at 725–900 °C and 0.01–0.223 s −1 strain rate, so the alloy can obtain the required defect-free structure and excellent machinability. The alloy microstructure was analyzed using the electron backscatter diffraction, and the main texture of the Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy deformed at 800 ℃ is the {011}< 100 > Goss texture, which is replaced by the {011}< 211 > brass texture at 900 °C. Recrystallization is promoted by higher deformation temperature. The recrystallization process provides energy for recrystallization by consuming dislocations, and the geometrically necessary dislocation density decreases with temperature. Transmission electron microscopy of the alloy shows that the precipitates are mainly Cu and NiTi phases. The interface between the two precipitated phases is semi-coherent. The precipitated phase at a semi-coherent interface can produce smaller elastic stress and lower interfacial energy, thus improving the refinement rate. Meanwhile, the Cu and NiTi phases have high toughness, and grain refinement can effectively improve the strength and hardness of the alloy. Graphical Abstract: ga1 Highlights: Hot deformation and constitutive equation of Cu-1.0Ni-0.9Sn-0.5Ti-0.3Cr alloy were investigated. The activation energy Q was determined as 404.15 kJ/mol. The texture changes from {011} < 100 > Goss texture at 800 °C to {011} < 211 > brass texture at 900 °C, the texture intensity decreases with the increase of deformation temperature. The precipitates of the Cu-1Ni-0.9Sn-0.5Ti-0.3Cr alloy are mainly the Cu and NiTi phases, and the interface between the two precipitates is semi-coherent.